Peranan Kantor Otoritas Bandar Udara Wilayah Iii Dalam Mengawasi Balon Udara Demi Menjaga Keamanan Dan Keselamatan Penerbangan - Falah Maulana Pujangga Putra Pratama (Pusat Riset dan Inovasi Nasional, 2023)
One of the objects monitored by the Airport Authority is the activity of hot air balloons in the air space. The presence of an uncontrolled hot air balloon certainly results in disruption of the aircraft flight path which will cause flight safety to be threatened. Therefore, all forms of disruption to the flight path that have the potential for danger must be handled immediately to ensure flight safety. This study aims to find out the role and constraints experienced by the Airport Authority Office Region III in supervising hot air balloons in order to maintain flight security and safety. This study uses qualitative methods with primary and secondary data collection techniques. The data used are observation, interviews, documentation and literature study to find out the role of the Region III Airport Authority Office in supervising hot air balloons. The results of this study indicate that the role played by the Region III Airport Authority Office in supervising hot air balloons has been carried out properly and has implemented according to the regulations stated in PM 41 of 2011 and PM 40 of 2018. Meanwhile the obstacles experienced were limited personnel, Budget that is less than optimal, Momentum for hot air balloon flights that are quite a lot and occur simultaneously, Community resistance to existing regulations, and a wide scope of supervision.